IMPLEMENTASI PENGGUNAAN MEDIA VIDEO ANIMASI ISLAMI DALAM PEMBELAJARAN KISAH NABI DAN RASUL PADA ANAK USIA DINI DI RA PERWANIDA 2 PALEMBANG - Sastia Putri, Nadia; Hamzah, Amir; Muhtarom (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Learning the stories of Prophets and Messengers for early childhood requires engaging learning media so that Islamic values can be well understood. One of the media that can be utilized is Islamic animated video. This study aims to examine the implementation of Islamic animated video media in learning the stories of Prophets and Messengers for early childhood at RA Perwanida 2 Palembang. This research employed a qualitative approach with a descriptive method. Data collection techniques included observation, interviews, and documentation. The results indicate that the use of Islamic animated video media was implemented through several stages, namely lesson planning by preparing the Daily Lesson Plan (RPPH), learning implementation through the presentation of Islamic animated videos according to the learning theme, and learning evaluation through question-and-answer activities and observation of children’s responses. The use of this media was able to increase children’s learning interest, attention, and understanding of the stories of Prophets and Messengers. Therefore, Islamic animated video media is effective to be applied